Towards a predictive simulation of brace action in adolescent idiopathic scoliosis. Issue 8 (11th June 2021) - Vergari, Claudio; Chen, Zhuowei; Robichon, Léopold; Courtois, Isabelle; Ebermeyer, Eric; Vialle, Raphaël; Langlais, Tristan; Pietton, Raphaël; Skalli, Wafa
Abstract: Bracing is the most common treatment to stop the progression of adolescent idiopathic scoliosis. Finite element modeling could help improve brace design, but model validation is still a challenge. In this work, the clinical relevance of a predictive and subject-specific model for bracing was evaluated in forty-six AIS patients. The model reproduces brace action and the patient's spinopelvic adjustments to keep balance. The model simulated 70% or more patients with geometrical parameters within a preselected tolerance level. Although the model simulation of the sagittal plane could be improved, the approach is promising for a realistic and predictive simulation of brace action.